Handling Instance Spanning Constraints in Compliance Management - Amin, Ruhul (ABC Journal of Advanced Research, 2019)
Instance spanning constraints refers to instruments to establish controls during multiple instances in or several processes. Many business entities crave an established ISC support system. Take, for instance, the bundling and unbundling of cargo from various logistics processes or the dependence of various examinations in medical treatment systems. During such systems, non-compliance with the ISC would lead to immense consequences and penalties, which can be fatal if it occurs in the medical field. ISC can also occur from process execution logs. Business execution store execution information for the process instance and, consequently, the characteristics of the execution logs. Discovering ISC early enough helps in supporting ISC design and execution. The purpose of this study is to contribute towards the categorization of the ISC and hence contribute to the digitalized ISC and its compliance management.